ANATOMI PERBANDINGAN KAYU CENDANA (SANTALUM ALBUM L.) DAN EXOCARPUS (EXOCARPUS LATIFOLIA R. Br.) - Y I Mandang (Pusat Penelitian dan Pengembangan Hasil Hutan, 1988)
Compared to Santalum album L., the wood of Exocarpus Latifolia R.Br. is lower in quality. It is there necessary to investigate the difference of their wood features to overcome the unwanted substitution or fraud possibilities.Microscopic study reveals that there are many similarities in wood anatomy between Santalum album L. and Exocarpus latifolia R. Br. They are anatomically different only in pore diameter and pore frequency. The wood of Exocarpus latifolia R.Br. has larger pore diameter but lower pore frequency. Some differences were also ob1erved on gross features of wood. Exocarpus latifolia R. Br. has darker sapwood color, coarser wood texture and less aromatic odour.